Uma proposta pedagógica de resolução de problemas para o ensino da matemática - MORAES, Rafaela Campos (2022)
The work is the result of research that verifies the importance of problem solving as a methodological approach to the teaching and learning of mathematics of students in the sixth year of elementary school. For this purpose, it uses, primarily, the bibliographic study. As a consequence of the theoretical-methodological approach, a proposal for a pedagogical intervention is presented, which involves the elaboration and planning of a Didactic Sequence. The conclusion allows to review the main aspects of the research that helped the construction of the essay and confirms the possibility of creating pedagogical proposals based on the problem solving theme.